2009
DOI: 10.1111/j.1740-8261.2009.01603.x
|View full text |Cite
|
Sign up to set email alerts
|

3d Conformal Radiation Therapy for Palliative Treatment of Canine Nasal Tumors

Abstract: We evaluated the response of 38 dogs treated with a coarsely fractionated, palliative radiation protocol based on CT-based 3D treatment planning. Dogs with histologically confirmed malignant nasal tumors were studied. Treatment prescriptions consisted of 3-4 x 8 Gy, 4-5 x 6 Gy, or 10 x 3 Gy fractions. Selected patient and tumor factors were evaluated for an effect on outcome. Resolution of clinical signs was reported after irradiation in all dogs. Acute toxicities were mild and short lived. Thirty-seven of 38 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 19 publications
3
38
1
Order By: Relevance
“…). Two studies of dogs receiving hypofractionated radiation protocols showed that 79 to 81% of treated dogs presented with late stage tumours (Buchholz , Maruo et al . ); however, these treatment groups do not represent the entire presented population of dogs as hypofractionated protocols are commonly recommended for dogs with late stage tumours.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…). Two studies of dogs receiving hypofractionated radiation protocols showed that 79 to 81% of treated dogs presented with late stage tumours (Buchholz , Maruo et al . ); however, these treatment groups do not represent the entire presented population of dogs as hypofractionated protocols are commonly recommended for dogs with late stage tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Our median survival times of 114 days with medical palliation and 174 days for hypofractionated radiotherapy protocols were also comparable with previous studies (Mellanby et al . , Buchholz , Maruo et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reported prognostic factors are destruction of the cribriform plate [1], tumor type [1,27], tumor stage [1,3,4,9,11,27], age >10 years [11], regional lymph node or pulmonary metastasis [8], resolution of clinical signs after treatment [7,23], tumor regression [28], facial deformity [23], three or more treatments/week [30] and a cumulative minimum tumor dose of at least 37 Gy [30]. In regard to the stage in particular, various stage classifications have been reported, and lower stages resulted in longer survival than higher stages [1,3,4,9,11,27]. However, the present results and other hypofractionated protocols [7,18] also showed no significant difference between tumor stage and survival time; thus, it was thought that the hypofractionated protocol was inappropriate for early stages.…”
Section: Discussionmentioning
confidence: 99%